A feasibility randomised control trial of individual cognitive stimulation therapy for dementia: impact on cognition, quality of life and positive psychology. (27th May 2021) - Gibbor, Luke; Forde, Lycia; Yates, Lauren; Orfanos, Stavros; Komodromos, Christina; Page, Harriet; Harvey, Kate; Spector, Aimee
Abstract: Objectives: This study aimed to evaluate the feasibility of a 14-session programme of individual Cognitive Stimulation Therapy (iCST) for people with dementia (PWD). It addressed potential limitations in previous literature of iCST and evaluated possible impact on cognition, quality of life (QoL) and positive psychology. Method: The 14-session iCST programme was developed using existing manuals for group and individual CST and consultation with experts in the field. Thirty-three PWD were recruited from care homes and randomly assigned to iCST (14, 45-min sessions) or treatment as usual (TAU) over seven weeks. Outcomes measures were assessed at baseline and follow-up after the intervention. Results: The intervention appeared feasible with high attendance to sessions, minimal levels of attrition, and ease of recruitment. Analysis of covariance indicated significant improvements in cognition (Alzheimer's Disease Assessment Scale-Cognitive subscale) for PWD receiving iCST compared to TAU. There were no significant differences between groups on follow-up scores on the standardised Mini Mental State Examination, measures of positive psychology or self- and proxy- reported QoL. Conclusion: A 14-session programme of iCST delivered by professionals was feasible and acceptable to PWD and may provide benefits to cognition. A larger randomised control trial would be necessary to fully evaluate intervention impact on cognition, as well as QoL and positive psychology.